Ultrasound Duplex Scanning of Vessels in the Diagnosis of Limb Length Discrepancy in Pediatric Patients with Congenital Vascular Malformations - Vyderko, R.V.; Zyma, A.M.; Chernukha, L.M.; Huch, A.O.; Huk, Yu.M.; Cheverda, A.I.; Kashyrova, O.V.; Kincha-Polishchuk, T.A.; Zotia, A.V. (TERRA ORTHOPAEDICA, 2024)
Summary. Background. Congenital vascular malformations (СVM) of the lower extremities can affect the longitudinal growth of the affected limb in pediatric patients. The influence of the regional blood flow disturbance on the formation of the limb length discrepancy (LLD) in CVM remains insufficiently studied. Objective: to study changes in regional blood flow based on color duplex angioscanning (CDA) of the main arteries of the lower extremities and to establish their influence on the formation of LLD in pediatric patients with CVM of the lower extremities. Material and Methods. The study included 36 pediatric patients with CVM of the lower extremities. The patients were divided according to the working classification scheme for the CVM (“VASC+T”): 23 arteriovenous, 7 venous, 4 capillary, and 2 lymphatic. The length of the lower extremities was assessed to determine the LLD. CDA of the main arteries of the lower extremities and soft tissues in the area of the knee joint was performed; blood flow velocity and pulsatility index (Pi) were evaluated. Results. LLD was diagnosed in 26 (72.2%) patients, while lengthening of the affected limb was observed in 21 (58.3%) patients and shortening was noted in 5 (13.8%) patients. In patients with a diffuse form of an arteriovenous malformation (AVM), the elongation of the affected limb was 2.76±1.54 cm, at the expense of the femur of 1.13±0.55 cm and at the expense of the tibia of 1.62±1.2 cm; LLD due to the elongation of individual segments of the affected limb was statistically insignificant (p = 0.192). In the case of diffuse form of AVM, an increase in blood flow velocity of the posterior tibial artery and a decrease in Pi in the popliteal and posterior tibial arteries of the affected limb were detected (p = 0.05). An increase in the total elongation of the affected limb with increased blood flow velocity on the superficial femoral artery was found, as well as an increase in the elongation of the affected limb with a decrease in Pi on the superficial femoral, popliteal, and posterior tibial arteries (p = 0.05). Conclusions. The study of regional blood flow of the lower extremities and LLD, which is the main orthopedic manifestation in patients with AVM, allows to establish the influence of hemodynamic disorders on the formation of orthopedic pathology in this category of patients. CDA in patients with diffuse form of AVM revealed a statistically significant increase in blood flow velocity in the posterior tibial artery, a decrease in the peripheral resistance (Pi) of the popliteal and posterior tibial arteries on the affected limb. Elongation of the affected limb with an increase in blood flow velocity on the superficial femoral artery, as well as a decrease in Pi on the superficial femoral, popliteal and posterior tibial arteries suggests a relationship between changes in regional blood circulation and LLD in patients with AVM.